Schaum's outline series feedback and control systems: Continuous (analog) and discrete (digital) - DiStefano, Joseph J.; Stubberud, Allen R.; Williams, Ivan J. (New York McGraw - Hill, 1990)
In this second edition, as in the first, we present a concise, yet quite comprehensive, treatment of the fundamentals of feedback and control system theory and applictions, for engineers, physical, biological and behavioral scientists, economists, mathematicians and student of these disciplines.
Keywords: Khoa học Máy tính